In vitro EVALUATION OF ANTIPROLIFERATIVE AND ANTIOXIDANT ACTIVITIES OF METHANOLIC EXTRACTS OF Gracilaria corticata AND Gracilaria foliifera AGAINST BREAST CANCER CELLS (Applied Biological Research, 2023)
The present study was aimed to assess the methanolic extracts of  Gracilaria corticata and G. foliifera for anti-proliferative and anti-oxidant  potency against breast cancer cell line MDA-MB-231. The antitumor  activity of G. corticata methanolic extract (GCME) and G. foliifera methanolic extract (GFME) against MDA-MB-231 cells was assessed by 3- (4,5-dimethylthiazol-2-cyl)-2,5-diphenyltetrazolium bromide (MTT) assay. The extracts decreased cell viability of MDA-MB-231 cells with an  estimated half-maximal inhibitory concentration (IC50) of 0.18 ± 1 and  0.078 ± 1 for GFMEs; and 0.116 ± 1 and 0.107 ± 1 for GCMEs. GCME  significantly increased ROS level after 48 h of treatment and decreased  glutathione (GSH) level (p
Keywords: Antioxidant; antitumor; glutathione; Gracilaria sp; mitochondrial membrane potential